2022
DOI: 10.3390/horticulturae8020091
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Investigation of the Antioxidant and Cytotoxic Potential of Tabernaemontana ventricosa Hochst. ex A. DC. Leaf, Stem, and Latex Extracts

Abstract: Tabernaemontana ventricosa (Apocynaceae) a latex-bearing plant is used in traditional medicine for its therapeutic benefits in reducing fever and hypertension and wound healing. Due to limited information on the plant’s pharmacological activities, this study aimed to investigate the antioxidant potential of the leaf, stem, and latex extracts of T. ventricosa, using the Folin-Ciocalteu (total phenolics), aluminum chloride colorimetric (total flavonoids), 2,2-diphenyl-1-picrylhydrazyl (DPPH), and ferric reducing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…With regards to the rest of the phytoconstituents detected in the present study, another investigation on the ethanolic extracts of leaves of C. molle produced similar findings with the detection of tannins, flavonoids, saponins and phenols; however, that study also reported the absence of alkaloids [55]. The differences in phytochemical composition within the species may be attributed to variations in locality, climate, season and extraction methods [56,57]. Several reports on the phytochemical composition of other Combretum species including C. erythrophyllum, C. leprosum, Combretum album and Combretum glutinosum revealed the presence of similar phytoconstituents to the present investigation [49,50,58,59].…”
Section: Yield and Phytochemical Composition Of Leaf And Stem Extractssupporting
confidence: 83%
“…With regards to the rest of the phytoconstituents detected in the present study, another investigation on the ethanolic extracts of leaves of C. molle produced similar findings with the detection of tannins, flavonoids, saponins and phenols; however, that study also reported the absence of alkaloids [55]. The differences in phytochemical composition within the species may be attributed to variations in locality, climate, season and extraction methods [56,57]. Several reports on the phytochemical composition of other Combretum species including C. erythrophyllum, C. leprosum, Combretum album and Combretum glutinosum revealed the presence of similar phytoconstituents to the present investigation [49,50,58,59].…”
Section: Yield and Phytochemical Composition Of Leaf And Stem Extractssupporting
confidence: 83%
“…Free radical scavenging activity of the E. alba was estimated using DPPH assay with some modifications from Ref. [19].…”
Section: Antioxidant Activity: Dpph Assaymentioning
confidence: 99%
“…58 %). Naidoo and collaborators observed similar results when studying Tabernaemontana ventricosa stems and leaves’ extracts [16] . This difference may be explained by the fact that leaves are photosynthetic organs and they produce high concentrations of metabolites [17] .…”
Section: Resultsmentioning
confidence: 69%
“…Naidoo and collaborators observed similar results when studying Tabernaemontana ventricosa stems and leaves' extracts. [16] This difference may be explained by the fact that leaves are photosynthetic organs and they produce high concentrations of metabolites. [17] For the five studied plants, the extractions with the most polar solvents: EtOH (for B. halimifolia leaves) or a mixture EtOH-H 2 O (for the other tested samples) showed the best yields (1.77-41.4 %).…”
Section: Plant Extractsmentioning
confidence: 99%